2011
DOI: 10.1111/j.1365-2893.2011.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of chronic hepatitis B epidemiology and management issues in selected countries in the Middle East

Abstract: Experts from seven countries convened as a Specialist Panel for the Middle East to share information on practical issues relating to the epidemiology, diagnosis and management of chronic hepatitis B (CHB) infection. The Middle East is regarded as a region of high-to-intermediate epidemicity; however, infant vaccination programmes have successfully lowered the prevalence of hepatitis B infection in most countries to that of low-to-intermediate endemicity. Vaccine issues still to be addressed included improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 82 publications
1
20
0
1
Order By: Relevance
“…The seroprotection rate after booster vaccination is similar to the results reported in studies from Malaysia (94.0%), Thailand (98.6%) and Germany (97.2%-99.6%). 14,16,25 Moreover, 90.6% of the re-vaccinated subjects showed an anamnestic response to booster vaccination. Similar anamnestic response has been reported at 23 years after primary vaccination in a study from China.…”
Section: 21mentioning
confidence: 99%
See 4 more Smart Citations
“…The seroprotection rate after booster vaccination is similar to the results reported in studies from Malaysia (94.0%), Thailand (98.6%) and Germany (97.2%-99.6%). 14,16,25 Moreover, 90.6% of the re-vaccinated subjects showed an anamnestic response to booster vaccination. Similar anamnestic response has been reported at 23 years after primary vaccination in a study from China.…”
Section: 21mentioning
confidence: 99%
“…These findings are in accordance with results reported in other studies. 25 It has been shown that vaccine induces active production of anti-HBs antibody accompanied by HBsAg-specific immunological memory that provide continuous protection in the absence of antibody. 17,18 The persistence of immunological memory over 5 years after primary vaccination is apparent from rapid increases in antibody level following booster vaccination, even in subjects who have lost antibodies.…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations